Moraxella species isolated from blood cultures in Europe (MORAXEu): a multicentre study of epidemiology and antimicrobial susceptibility with complementary phylogenomic analysis of publicly available genomes - Tone Tønjum; Vinicius da Silva Franklin-Duarte; Johan Christian Berild; Konstantina Gartzonika; Eirini Christaki; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Nikolaos Giormezis; Gergana Lengerova; Yordan Kalchev; Ana Budimir; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Biodegradable and conventional microplastics differentially affect soil nutrient availability and stress responses in spinach (Spinacia oleracea L.) - Giorgia Santini; Lucia Santorufo; Giulia Costanzo; Carmen Arena; Simone Landi; Sergio Esposito; Gabriella Di Natale; Marco Trifuoggi; Giulia Maisto (Applied Soil Ecology, 2026)

The invasive algae Caulerpa racemosa poses a threat to mussel viability and reproduction - Luigi Rosati; Teresa Chianese; Rachele Macirella; Elvira Brunelli; Annamaria Locascio; Maria Sirakov; Alberto Macina; Marina Prisco; Simone Landi; Kristina Pogrmic-Majkic; Maria De Falco (Environmental Toxicology and Pharmacology, 2026)

Optimization of lithium diffusion modelling in plagioclase: implications for the assessment of pre-eruptive timescales - Simone Costa; Matteo Masotta; Fabio Colle; Pier Paolo Giacomoni; Claudia D’Oriano; Patrizia Landi (Chemical Geology, 2026)

Different seed priming techniques variously modulate pre-germinative metabolism and germination performance in three Capsicum annuum cultivars - Angelo Granata; Maria Cristina Sorrentino; Simone Landi; Anna Gaglione; Sergio Esposito; Fiore Capozzi; Valeria Spagnuolo (Plant Biosystems, 2026)

The hidden constrains in soil ecology and plant physiology: microplastic effects on nutrient and metal transport in soil-plant continuum - Simone Landi; Giorgia Santini; Noemi Russo; Lucia Santorufo; Karen Power; Luigi Rosati; Antonietta Siciliano; Alessandra Marano; Carmen Arena; Sergio Esposito; Giulia Maisto (Plant and Soil, 2025)

Lack of Arabidopsis chloroplastic glucose-6-phosphate dehydrogenase 1 (G6PD1) affects lipid synthesis during cold stress response - Simone Landi; Ermenegilda Vitale; Mariamichela Lanzilli; Carmen Arena; Giuliana D'Ippolito; Angelo Fontana; Sergio Esposito (Plant Science, 2024)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Nitrogen assimilation under different nitrate nutrition in Tunisian durum wheat landraces and improved genotypes - Sawsen Ayadi; Salma Jallouli; Simone Landi; Giorgia Capasso; Zoubeir Chamekh; Manuela Cardi; Valeria Paradisone; Marco Lentini; Chahine Karmous; Youssef Trifa; Sergio Esposito (Plant Biosystems, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Early responses to cadmium exposure in barley plants: effects on biometric and physiological parameters - Marco Lentini; Alessia De Lillo; Valeria Paradisone; Daniela Liberti; Simone Landi; Sergio Esposito (Acta Physiologiae Plantarum, 2018)

Correction to: CrystalMom: a new model for the evolution of crystal size distributions in magmas with the quadrature-based method of moments - Simone Colucci; Mattia de’ Michieli Vitturi; Patrizia Landi (Contributions to Mineralogy and Petrology, 2018)

CrystalMom: a new model for the evolution of crystal size distributions in magmas with the quadrature-based method of moments - Colucci Simone; de’ Michieli Vitturi Mattia; Landi Patrizia (Contributions to Mineralogy and Petrology, 2017)